Conditions for spin-gapless semiconducting behavior in Mn2CoAl inverse Heusler compound - Galanakis, I.; Ozdogan, K.; Sasioglu, E.; Bluegel, S. (AMER INST PHYSICS, 2014)
Employing ab initio electronic structure calculations, we investigate the conditions for spin-gapless semiconducting (SGS) behavior in the inverse Mn2CoAl Heusler compound. We show that tetragonalization of the lattice, which can occur during films growth, keeps the SGS character of the perfect cubic compound. On the contrary, atomic swaps even between sites with different local symmetry destroy the SGS character giving rise to a half-metallic state. Furthermore, the occurrence of Co-surplus leads also to half-metallicity. Thus, we propose that in order to achieve SGS behavior during the growth of Mn2CoAl (and similar SGS Heusler compounds) thin films, one should minimize the occurrence of defects, while small deformations of the lattice, due to the lattice mismatch with the substrate, do not play a crucial role. (C) 2014 AIP Publishing LLC.
Keywords: BAND-STRUCTURE; Physics